Hepatocellular Adenoma Risk Factors of Hemorrhage: Size Is Not the Only Concern!. Issue 5 (November 2021) - Julien, Céline; Le-Bail, Brigitte; Ouazzani Touhami, Kevin; Frulio, Nora; Blanc, Jean-Frédéric; Adam, Jean-Philippe; Laurent, Christophe; Balabaud, Charles; Bioulac-Sage, Paulette; Chiche, Laurence
Abstract : Objective: Our aim was to determine independent risk factors of clinical bleeding of hepatocellular adenoma (HCA) to define a better management strategy. Summary Background Data: HCA is a rare benign liver tumor with severe complications: malignant transformation that is rare (5%–8%) and more often, hemorrhage (20%–27%). To date, only size > 5 cm and histological subtype (possibly sonic hedgehog) are associated with bleeding, but these criteria are not clearly established. Methods: We retrospectively collected data from a cohort of 268 patients with HCA managed in our tertiary center, from 1984 to 2020 and focused on clinical bleeding. Hemorrhage was considered severe when it required intensive care and moderate when bleeding symptoms required a hospitalization. We included 261 patients, of whom 130 (49.8%) had multiple HCAs or liver adenomatosis. All surgical specimen and liver biopsy were reviewed by an experienced liver pathologist and reclassified in the light of the current immunohistochemistry. Mean duration of follow-up was 93.3 months (range 1–363). We analyzed type, frequency, consequences of bleeding, and risk factors among clinical data and HCA characteristics. Results: Eighty-three HCA (31.8%) were hemorrhagic. There were 4 pregnant women with 1 newborn death. One patient died before treatment. Surgery was performed in 78 (94.0%) patients. Mortality was nil and severe complications occurred in 11.5%. Multivariate analysis identified size (OR 1.02 [1.01–1.02], P < 0.001), shHCA (OR 21.02 [5.05–87.52], P < 0.001), b-catenin mutation on exon 7/8 (OR 6.47 [1.78–23.55], P = 0.0046), chronic alcohol consumption (OR 9.16 [2.47–34.01], P < 0.001) as independent risk factors of clinical bleeding. Conclusions: This series, focused on the hemorrhagic risk of HCA, shows that size, but rather more molecular subtype is determinant in the natural history of HCA. Abstract : Supplemental Digital Content is available in the text